Comparative antifungal efficacy of Zinnia elegans and Tithonia diversifolia extracts against Fusarium verticillioides: In-vitro study (Wallacea Plant Protection Journal, 2026)
Fusarium verticillioides are broad-spectrum pathogens with extensive host ranges and represent a major constraint in agricultural production. Synthetic pesticides are commonly used by farmers to manage Fusarium-induced diseases; however, their intensive application poses serious risks to environmental sustainability and human health. Consequently, the development of eco-friendly disease management strategies is urgently required. Botanical pesticides derived from plant extracts represent a promising alternative. This study evaluated the antifungal effectiveness of Mexican sunflower (Tithonia diversifolia) and zinnia (Zinnia elegans) extracts at different concentrations against Fusarium wilt. The experiment was conducted from September to December 2024 using a completely randomized design (CRD) with six extract treatments (1800, 3600, and 5400 ppm for each plant species) and an untreated control. Antifungal activity was assessed based on the percentage of mycelial growth inhibition. The results demonstrated that both extract type and concentration significantly affected fungal inhibition (p ≤ 0.05). Extract of Z. elegans at 5400 ppm exhibited the highest inhibitory effect, suppressing Fusarium growth by 32.0%, which was significantly higher than all other treatments. In contrast, T. diversifolia extract showed moderate inhibition, with a maximum of 16.5% inhibition at 5400 ppm. The increasing inhibition with higher concentrations indicates a clear dose-dependent response. These findings highlight the scientific significance of plant-based extracts as natural antifungal agents and demonstrate the superior efficacy of Z. elegans extract at higher concentrations. Overall, this study underscores the strong potential of zinnia-based extracts as eco-friendly biofungicide candidates for sustainable management of Fusarium wilt diseases.
Keywords: Botanical pesticide; Fusarium spp.; Plant extract; Tithonia diversifolia; Zinnia elegans